INTERVIEW WITH LUIS BEDOYA REYES - Seiner, Lizardo A. (2020)
Luis Bedoya Reyes, great experienced and speaker politician, generates an important repercussion in the Peruvian political life. In this interview, rather than focus on conjunctural aspects of current politics, is oriented on his life experiences, that only a man like Luis Bedoya Reyes can share. Reflections are expressed about human dignity, cooperation between politicians, and freedom, as factors to achieve more development and productivity for Peru.